PEDAGOGICAL MECHANISMS THAT PROVIDE PROFESSIONAL FORMATION OF FUTURE PHYSICAL EDUCATION TEACHERS THROUGH NATIONAL MOVEMENT GAMES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article presents some thoughts on pedagogical mechanisms that provide professional formation of future physical education teachers through national movement games. The use of national games in educational processes and teaching them to perform them independently increases students' interest in the lesson. Students feel creative enthusiasm. At the same time, they get acquainted with our cultural heritage, learn our ancient terms and expressions.